Upravljavska sposobnost lokalnih samoupravnih skupnosti - Rožen, Tomaž (Local Democracy, 2015)
Local communities have an important role in society. According to states legislature they execute local public policies. Those processes include local democracy, public administration, local economy and social entities. Also they combine public and private resources. All of these groups of factors have their own capacity. Capacity is their ability to achieve goals and consists from inside and outside factors. Capacity of local self-government is integrated capacity. It represents holistic capacity for those units. It tells us, whether they are capable of doing things they should do, according to social and political system and its demands. Local units have different level of capacity. With conceptual model and field research we tested our research hypothesis. Our hypothesis is that local self-government communities with higher capacity offer their residents broader local public services and goods. Also we studies influence of political stability and autonomy on capacity. On representative sample of municipalities in Republic of Slovenia we confirmed all ours research hypothesis. Conceptual model of capacity is a tool for analysing individual communities and for analysing the whole system of local-self government. Also many suggestions for improvement can be made.